Conformational changes in dough and bread from wheat flour with the addition of oat bran in combination with phospholipids - Shevchenko, Anastasiia; Litvynchuk (Vorontsova), Svitlana; Drobot, Vira (My University, 2023)
The purpose of the research was to determine the influence of oat bran in combination with sunflower lecithin on conformational changes in the structure of dough semi-finished products and bread made from wheat flour. After kneading the dough, no conformational changes were observed, and during the fermentation process, they deepened with an increase in the percentage of replacement of wheat flour with oat bran. The spectra of bread had a lower reflectance than the dough samples both after kneading and during fermentation. The protein of such bread is more fully used for anabolic needs by the body. The biological value of bread with oat bran is higher, which makes them a promising raw material not only from the point of view of enriching bakery products with valuable nutrients, but also of a higher degree of their digestibility
Keywords: oat bran; sunflower lecithin; bread; dough; conformational transformations; кафедра технології хлібопекарських і кондитерських виробів; кафедра фізики та професійної безпеки